The Effect of Guided Discovery Learning Models Assisted by PhET Simulation on the Mastery of Concepts and Students' Capabilities in Solving Physics Problems - Rizka Sofiya; Gunawan Gunawan; Kosim Kosim; Hikmawati Hikmawati (Indonesian Publication Center, 2020)
This study aims to examine the effect of guided discovery learning models assisted by PhET simulations on the mastery of physics concepts and students' problem-solving abilities. This quasi-experimental study uses a nonequivalent multiple group design. This study population was all grade X students in one of the high schools in Narmada, West Lombok. Two sample classes were treated with guided discovery learning models. One class was assisted by PhET simulation media while the other class was not assisted by PhET simulation media. Concept mastery data were obtained using multiple-choice tests, while problem-solving ability data was obtained using essay tests. The results showed that the mastery of concepts and problem-solving abilities of students who learned PhET-assisted simulation were higher than other classes. The research hypothesis was tested using the MANOVA test with a significance level of 5%. It concluded that there was an influence of the guided discovery learning model assisted by PhET simulations on the mastery of physics concepts and students' problem-solving abilities.